BERDAYA, MEMPERDAYA, ATAU DIPERDAYA: BAGAIMANA PEREMPUAN DIPOSISIKAN DALAM VIDEO MUSIK PETERPAN BERJUDUL “KU KATAKAN DENGAN INDAH” DAN “KHAYALAN TINGKAT TINGGI” - Agnurhasta, Azzan Wafiq; Halil, Citra Buana; Basyir, Jalaludin (JURNAL SIPAKALEBBI, 2023)
This research aimed to explain how women are positioned within two music videos of Peterpan, “Ku Katakan Dengan Indah” and “Khayalan Tingkat Tinnggi”. The research used popular music studies in relation with gender and sexuality. The data of this research were two Peterpan’s music videos from their second album, Bintang di Surga, entitled “Ku Katakan Dengan Indah” and “Khayalan Tingkat Tinggi”. To analyse the data, this research used musical discourse analysis as a tool. The findings showed that women were always positioned as troubles for men within the domination of patriarchy. When women were portrayed as a powerful subject, they used the power to manipulate men around them in “Ku Katakan Dengan Indah”. While womenn were portrayed as men’s fantasy object in “Khayalan Tinngkat Tinggi”, they brought troubles for men around them as they made them crazy in love. From the lyrical, musical, and visual aspects, these songs show the domination of masculinity in the form of cock rock phenomenon.